The grab [videorecording (DVD)] - Cowperthwaite, Gabriela; Halverson, Nathan; Muñoz, JoeBill; Newman, Mallory; Ritsher, David; Schwartz, Emma C. (Magnolia Pictures, 2024)
An investigative journalist uncovers the money, influence, and alarming rationale behind covert efforts to control the most vital resource on the planet, in the latest expose from filmmaker Gabriela Cowperthwaite (Blackfish).